(untitled) (PERcursos Linguísticos, 2022)
This article aims to present some historiographical notes on an important process that took place in translation criticism at the beginning of the 19th century: the consolidation of the renown of a translator in the French literary milieu. Based on the Historiography of Discourses on Translation, a series of critical reviews of the Journal des Débats were analyzed. It was noticed that, in a dispute between the critics Dussault and Féletz, from which the latter emerged victorious, Delille became a translation celebrity in 19th century France.